2022
DOI: 10.2147/opth.s391355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Postoperative Total Ocular Aberrations After Bilateral Implantation of Monofocal IOL with Extended Depth of Focus in Phacoemulsification

Abstract: To evaluate postoperative visual performance and total ocular aberration in cataract patients after implantation of the TECNIS Eyhance™ intraocular lens (IOL). Methods: Our study is a prospective interventional non-comparative study that was conducted on 34 eyes of 17 patients who underwent phacoemulsification and Eyhance IOL implantation. Postoperative corrected and uncorrected near and far visual acuity and total ocular aberration were assessed 3 months after surgery. Results: Our study included 34 eyes of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…de Luis Eguileor et al [ 17 ] identified a significant correlation between SA and UIVA, endorsing that with SA of intermediate values, the ICB00 offers better UIVA, which is consistent with the results of this study. Most recently, Abd Elghaffar Shehata et al [ 18 ] found that postoperative ICB00 SA ranging between 0.2 and 0.25 gives the minimum reading add (+ 0.75 D).…”
Section: Discussionmentioning
confidence: 99%
“…de Luis Eguileor et al [ 17 ] identified a significant correlation between SA and UIVA, endorsing that with SA of intermediate values, the ICB00 offers better UIVA, which is consistent with the results of this study. Most recently, Abd Elghaffar Shehata et al [ 18 ] found that postoperative ICB00 SA ranging between 0.2 and 0.25 gives the minimum reading add (+ 0.75 D).…”
Section: Discussionmentioning
confidence: 99%